Rotenone Treatment Reveals a Role for Electron Transport Complex I in the Subcellular Localization of Key Transcriptional Regulators During T Helper Cell Differentiation - Ozay, Emrah Ilker; Sherman, Heather L.; Mello, Victoria; Trombley, Grace; Lerman, Adam; Tew, Gregory N.; Yadava, Nagendra; Minter, Lisa M. (Frontiers in Immunology, 2018)
Recent advances in our understanding of tumor cell mitochondrial metabolism suggest it may be an attractive therapeutic target. Mitochondria are central hubs of metabolism that provide energy during the differentiation and maintenance of immune cell phenotypes. Mitochondrial membranes harbor several enzyme complexes that are involved in the process of oxidative phosphorylation, which takes place during energy production. Data suggest that, among these enzyme complexes, deficiencies in electron transport complex I may differentially affect immune responses and may contribute to the pathophysiology of several immunological conditions. Once activated by T cell receptor signaling, along with co-stimulation through CD28, CD4 T cells utilize mitochondrial energy to differentiate into distinct T helper (Th) subsets. T cell signaling activates Notch1, which is cleaved from the plasma membrane to generate its intracellular form (N1ICD). In the presence of specific cytokines, Notch1 regulates gene transcription related to cell fate to modulate CD4 Th type 1, Th2, Th17, and induced regulatory T cell (iTreg) differentiation. The process of differentiating into any of these subsets requires metabolic energy, provided by the mitochondria. We hypothesized that the requirement for mitochondrial metabolism varies between different Th subsets and may intersect with Notch1 signaling. We used the organic pesticide rotenone, a well-described complex I inhibitor, to assess how compromised mitochondrial integrity impacts CD4 T cell differentiation into Th1, Th2, Th17, and iTreg cells. We also investigated how Notch1 localization and downstream transcriptional capabilities regulation may be altered in each subset following rotenone treatment. Our data suggest that mitochondrial integrity impacts each of these Th subsets differently, through its influence on Notch1 subcellular localization. Our work further supports the notion that altered immune responses can result from complex I inhibition. Therefore, understanding how mitochondrial inhibitors affect immune responses may help to inform therapeutic approaches to cancer treatment.